Les journalistes des télévisions privées algériennes en 2015 : Nouvelles figures, nouvelles pratiques - Nabila Aldjia Bouchaala (L’Année du Maghreb)
This article examines the socio-professional conditions of private media journalists in Algeria according to the representations they made of their professional practices; in light of Pierre Bourdieu’s development of the notion of the journalistic field. The survey on about twenty journalists, belonging to six media companies, intended to settle their practices in the context of the appearance of these television channels, so that the objective underlying this work is to understand the new configuration of the audiovisual landscape and see the role played by journalists in its definition.